2021
DOI: 10.3390/ijerph18189425
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Capillary Blood Gases in Medical Personnel Caring for Patients Isolated Due to SARS-CoV-2 in Intensive Care Units before and after Using Enhanced Filtration Masks: A Prospective Cohort Study

Abstract: The dynamically changing epidemiological situation caused by the SARS-CoV-2 virus is associated with the increased burden and fatigue of medical personnel. The aim of the study was to evaluate: (1) oxygen and carbon dioxide blood pressure and saturation levels in medical personnel caring for patients isolated due to SARS-CoV-2 in ICUs; (2) adverse symptoms reported by medical personnel after leaving the isolation zone. Design: A Prospective Cohort Study. Methods: The project was implemented in the first quarte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
3
2
0
Order By: Relevance
“…13,16 Most studies have shown that respirator use does not lead to significant changes in pCO 2 levels. [12][13][14] The fact that pCO 2 levels were not impaired in our current study corroborates evidence in the published literature. However, our study contradicts other evidence in the published literature regarding side effects related to mask use.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…13,16 Most studies have shown that respirator use does not lead to significant changes in pCO 2 levels. [12][13][14] The fact that pCO 2 levels were not impaired in our current study corroborates evidence in the published literature. However, our study contradicts other evidence in the published literature regarding side effects related to mask use.…”
Section: Discussionsupporting
confidence: 92%
“…13 A study conducted with 57 nurses and 47 paramedics working in the SARS coronavirus-2 intensive care unit showed that the use of FFP2 and FFP3 respirators did not cause deterioration in blood gas values in a median time of 240 minutes. 14 The results of these 2 studies are similar to our findings.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Several studies evaluated the short-term influence of surgical masks and FFP masks on gas exchange or respiratory work [5][6][7][8][9]. In the largest study performed thus far, Medrzycka-Dabrowska et al evaluated capillary blood gas analysis in 110 nurses and paramedics before and after wearing PPE for 4 hours [7]. There was no significant difference in the blood gas values analysed.…”
Section: Introductionmentioning
confidence: 99%
“…In the largest study performed thus far, M edrzycka -D abrowska et al . [ 7 ] evaluated capillary blood gas analysis in 110 nurses and paramedics before and after wearing PPE for 4 h. There was no significant difference in the blood gas values analysed. However, 29% of the participants reported negative symptoms such as fatigue or drowsiness.…”
Section: Introductionmentioning
confidence: 99%